Consumo simbólico do futebol americano em transmissões brasileiras: hibridizações discursivas e estratégias de produção - Storel, Thalita Fomin (2023)
American football, a traditional sport in the United States, has gained popularity among Brazilian viewers and consumers in recent decades. Its impact can be felt in the cultural, social, and political spheres both in the US and Brazil. This impact has been facilitated by the context of symbolic consumption and technological advancements that allow for adjusted broadcasts. Using French Discourse Analysis, this research investigates the discursive hybridization processes present in American football broadcasts in Brazil. The resulting map demonstrates that the hybridization in these broadcasts results from the union of factors that form a hybrid discursive structure. These factors include the discourses that legitimize sport in American culture, symbols of Brazilian culture, intertextual humor and teaching, as well as the discursive and linguistic resources of catchphrases, hyperboles, analogies, and celebrities.